2009
DOI: 10.1002/etep.348
|View full text |Cite
|
Sign up to set email alerts
|

Electricity pricing and market power—evidence from Germany

Abstract: The aim of this paper is to develop a methodology for measuring the exercise of potential market power in liberalized electricity markets. We therefore investigate producer behavior in the context of electricity pricing with respect to fundamental time-dependent marginal cost (TMC), i.e. CO 2 -and fuel cost. In doing so, we do not -in contrast to most current approaches to market power investigation -rely on an estimate of the entire generation cost, which inevitably suffers from the lack of appropriate availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Although only about 25% of the German electricity is traded in the spot market (Pietz, 2009), the EEX spot price forms the basis for prices of other contracts and could therefore be regarded as the central German marketplace (Möller, 2010;Möst and Genoese, 2009). The EEX spot market is a price auction where the market clearing price corresponds to the variable costs, or short run marginal costs (SRMC), of the marginal power plant needed to cover the demand (Janssen and Wobben, 2009). 6 The mix of technologies in the German power system could be categorized into five groups in terms of variable production costs (SRMC) ability of short term regulation and role in the power system, as represented in Table 1.…”
Section: The German Power Market and The Merit Order Effectmentioning
confidence: 99%
“…Although only about 25% of the German electricity is traded in the spot market (Pietz, 2009), the EEX spot price forms the basis for prices of other contracts and could therefore be regarded as the central German marketplace (Möller, 2010;Möst and Genoese, 2009). The EEX spot market is a price auction where the market clearing price corresponds to the variable costs, or short run marginal costs (SRMC), of the marginal power plant needed to cover the demand (Janssen and Wobben, 2009). 6 The mix of technologies in the German power system could be categorized into five groups in terms of variable production costs (SRMC) ability of short term regulation and role in the power system, as represented in Table 1.…”
Section: The German Power Market and The Merit Order Effectmentioning
confidence: 99%
“…There is evidence of regional market power in the electricity sector discussed in papers [7,21]. This means that the electricity producer has the possibility of setting a price for electricity above their marginal cost [6].…”
Section: Market Power Of the Electricity Producermentioning
confidence: 99%
“…The final report confirmed that the German wholesale electricity market undergone markups of 50% from 2003 to 2005. Janssen and Wobben [2009] took a different approach. Instead of relying on an estimate of the entire generation cost, they investigate producers' behaviors in the context of electricity pricing with respect to several time-dependent marginal costs (TMCs).…”
Section: Literature On Market Power In Germany's Wholesale Marketmentioning
confidence: 99%